CLASSROOM-BASED ASSESSMENT IMPLEMENTED BY HIGH SCHOOL TEACHERS TO IMPROVE STUDENTS’ ACHIEVEMENT IN LEARNING - Ida Ayu Made Sri Widiastuti (Jurnal Cakrawala Ilmiah, 2024)
Assessment must be conducted in the classroom and carried out as an integrated part of the teaching and learning process. This study determines the types and challenges of implementing classroom assessments in senior high schools. This qualitative study was conducted by interviewing selected high school teachers, and direct classroom observation was conducted to ensure the validity and reliability of the information related to the classroom assessment. This study found that teachers intensively conducted classroom assessments to know the student's learning progress and to maintain the high quality of learning and teaching processes. The teachers conduct Several types of assessments, such as performance Assessments, self-assessments, essays, portfolios, and project-based assessments. This study implies that teachers should continually implement classroom assessment intensively to improve students' achievement in learning.